Analysis of farmer welfare levels in Paluh Kemiri Village using Farmer Household Income Exchange Rate parameters - Hasibuan, Martua Raya; Qarni, Waizul; Daulay, Aqwa Naser (LPMP Imperium, 2025)
Paluh Kemiri Village, located in the Lubuk Pakam region of Indonesia, primarily relies on agriculture for its livelihood. However, residents face challenges such as limited resources, low income, and insufficient government support. The Farmer Household Income Exchange Rate (NTPRP) is a key indicator of their welfare. Research methods included observation and interviews to assess the farming community's happiness using NTPRP parameters. The minimum NTPRP value was 0.56, indicating that household expenditures exceeded income, making it difficult for farmers to meet both agricultural and non-agricultural needs. The maximum NTPRP value was 5.43, showing that some farmers could meet their needs. On average, the NTPRP was 1.31, suggesting that most farmers manage to afford their expenses. Additionally, data from BPS NTP North Sumatra in May 2025 indicated that farmers are experiencing a surplus with a value of 139.53. Public Interest Statement: Analyzing the welfare of farmers in Paluh Kemiri Village, Lubuk Pakam, is essential for understanding their economic and social conditions. This study uses the Farmer Household Income Exchange Rate (NTPRP) to identify challenges such as low income and limited resources. The findings are intended to guide the government and stakeholders in creating effective policies to improve farmers' welfare and promote sustainable agricultural development.